Utilization of Twitter Data in Deforestation Countermeasures in Pujon District, Malang Regency - Kurniawati, Risa Amalia Kurniawati; Nursida Arif; Bambang Syaeful Hadi; Hastuti; Dyah Respati Suryo Sumunar (Universitas Negeri Surabaya, 2024)
Big data such as Twitter data has been widely used in social science studies, but its use in deforestation studies is still rare in Indonesia. Therefore, the purpose of this research is to find out what information can be identified through Twitter social media data. The data used in this research is quantitative Twitter data. The geotagged Twitter data was also visualized in the form of maps to help the description analysis process, which is the main analysis in this study. The results of this study show that Twitter deforestation in Pujon Sub-district, Malang Regency has an impact on the surrounding vegetation and hydrological conditions. In the implementation of deforestation countermeasures, we argue that Twitter data can be used in all phases. Twitter data in deforestation countermeasures especially its influence on vegetation and hydrology conditions. Another weakness is that the information from the Twitter data is not certain whether it represents the same demographic characteristics as the conditions in the field and the level of validity of the information that cannot be accounted for yet.